2012
DOI: 10.1371/journal.pone.0035660
|View full text |Cite
|
Sign up to set email alerts
|

The Cobalamin-Binding Protein in Zebrafish Is an Intermediate between the Three Cobalamin-Binding Proteins in Human

Abstract: In humans, three soluble extracellular cobalamin-binding proteins; transcobalamin (TC), intrinsic factor (IF), and haptocorrin (HC), are involved in the uptake and transport of cobalamin. In this study, we investigate a cobalamin-binding protein from zebrafish (Danio rerio) and summarize current knowledge concerning the phylogenetic evolution of kindred proteins. We identified a cobalamin binding capacity in zebrafish protein extracts (8.2 pmol/fish) and ambient water (13.5 pmol/fish) associated with a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…The presence of just one soluble cobalamin-binding protein in trout is in accord with our previous study on zebrafish (7) and the database prediction for salmon. Trout HIT shares sequence identity with the zebrafish HIT protein (58.2%) and even more with its close relative, the salmon (91.3%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The presence of just one soluble cobalamin-binding protein in trout is in accord with our previous study on zebrafish (7) and the database prediction for salmon. Trout HIT shares sequence identity with the zebrafish HIT protein (58.2%) and even more with its close relative, the salmon (91.3%).…”
Section: Discussionsupporting
confidence: 88%
“…Blood samples were collected from the caudal tail vein into lithium heparin tubes, and plasma was removed after centrifugation at 2000 ϫ g for 10 min and stored at Ϫ20°C until analysis. Protein extractions of roe and tissue samples (ϳ1 ml of buffer per 1 g of tissue) were carried out by homogenization on ice as described previously (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish lack intrinsic factor, the main vitamin B 12 binding protein needed for absorption in humans. Greibe et al (2012) found that zebrafish and rainbow trout have only one vitamin B 12 binding protein, a structurally intermediate between the three vitamin B 12 binding proteins identified in human.…”
Section: Anorexiamentioning
confidence: 90%
“…Interestingly, in species lacking HC, including mice and lower vertebrates, a TC-like protein has been shown to be less specific for Cbl and to recognize Cbi and other corrinoids, similar to human HC (32)(33)(34). According to the sequence alignment (Figs.…”
Section: Discussionmentioning
confidence: 99%